Handmade Electronic Music : The Art Of Hardware Hacking - Collins, Nicolas, ....- (New York : Routledge, 2020)
Handmade Electronic Music: The Art of Hardware Hacking provides a long-needed, practical, and engaging introduction to the craft of making-as well as creatively cannibalizing-electronic circuits for artistic purposes. With a sense of adventure and no prior knowledge, the reader can subvert the intentions designed into devices such as radios and toys to discover a new sonic world. You will also learn how to make contact microphones, pickups for electromagnetic fields, oscillators, distortion boxes, mixers, and unusual signal processors cheaply and quickly. At a time when computers dominate music production, this book offers a rare glimpse into the core technology of early live electronic music, as well as more recent developments at the hands of emerging artists. This revised and expanded third edition has been updated throughout to reflect recent developments in technology and DIY approaches. New to this edition are chapters contributed by a diverse group of practitioners, addressing the latest developments in technology and creative trends, as well as an extensive companion website that provides media examples, tutorials, and further reading.
Keywords: Music Technology; Music